Prioritizing store plan alternatives produced with shape grammar using multi-criteria decision-making techniques - Ozdemir, Sahika; Ozdemir, Yavuz (SAGE PUBLICATIONS LTD, 2018)
To generate alternatives and variations of specific architectural models, shape grammars can be used by applying a set of geometric rules step by step. With the development in human life, advances in store design, design concept, commercial buildings' architectural and spatial fiction, the magazine of the interior, and facade design cause rising competition between stores and also between designers. For this reason, in this paper we study the evaluation of store plan alternatives produced with shape grammar using two of multi-criteria decision-making (MCDM) techniques with fuzzy numbers, namely fuzzy analytic hierarchy process and fuzzy analytic network process. The main contribution of this paper is to prioritize plan alternatives using numerical methods with experts' view. To the authors' knowledge, this will be the first interdisciplinary study which uses MCDM techniques for evaluating shape grammar outputs in architectural design.
Keywords: Computer aided design; shape grammars; store design; decision making; ANALYTIC NETWORK PROCESS; FUZZY AHP; PROJECT SELECTION; GENERATION; LOGISTICS; LANGUAGE; Environmental Sciences & Ecology; Geography; Public Administration; Urban Studies